Polysubstituted and ring-fused pyridazine systems from tetrafluoropyridazine. Issue 5 (2nd February 2017) - Pattison, Graham; Sandford, Graham; Wilson, Ian; Yufit, Dmitrii S.; Howard, Judith A.K.; Christopher, John A.; Miller, David D.
Abstract: Tetrafluoropyridazine1 reacts with a range of oxygen-, nitrogen-, sulfur- and carbon-centred nucleophiles to give, in general, products2 arising from substitution of fluorine para to ring nitrogen. Subsequent reaction of the trifluoropyridazine derivatives2 gave a range of 4, 5-di- and tri-substituted products3 and6 . Related reactions of tetrafluoropyridazine1 with difunctional nucleophiles gave [6, 6]-, [5, 6]- and [6, 5, 6]-polycyclic ring fused pyridazine scaffolds4 and9 . Further functionalisation of scaffolds4 by nucleophlic aromatic substitution processes involving displacement of fluorine atoms at activated sites ortho to ring nitrogen provide an indication of the synthetic possibilities offered using tetrafluoropyridazine as a starting material for the preparation of polysubstituted pyridazine and novel polyfunctional ring fused pyridazine systems with potential applications in the drug discovery arena. Graphical abstract: